Business improvement through artificial intelligence-based digital marketing driven mapping skills at UKM JAMARIS - Qristin Violinda; M. Anas Dzakiy; Ika Menarianti; Trisno Varida; Zalfa Nabila Agnaputri; Ely Aeni Dieka Prahesti; Azahra Salsabila Septianika (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2025)
This community service activity aims to increase the independence of the creative industry through Artificial Intelligence (AI)-driven digital transformation and skill mapping for the JAMARIS SME in Jatijajar Village. This SME, which operates in the creative sector, often struggles to maximize its business potential and compete in an increasingly digital market. Therefore, this training is designed to introduce AI technology and skill mapping as tools for more efficient business planning and management. Through this training, participants are equipped with basic skills in AI, including how to map existing skills within an organization and utilize data for more informed decision-making. After participating in the training, participants showed significant progress in mastering digital technology, with 85 percent of them able to utilize AI for market analysis and design more effective business strategies. In addition, 75 percent of SMEs reported increased efficiency in business management. The results of this activity indicate that AI-based digital transformation can strengthen SME competitiveness, increase productivity, and open up new opportunities for innovation in the creative industry of Jatijajar Village SMEs.